PENERAPAN PERLAKUAN AKUNTANSI ASET TETAP BERDASARKAN PSAK NO. 16 PADA HOTEL ARVIEL GORONTALO - Chandra, Vionalisa; Ilat, Ventje; Kalalo, Meily Y. B. (Universitas Sam Ratulangi, 2020)
Assets remain the most important part in supporting the company's operational activities, especially for companies engaged in the hotel industry. Therefore, it is necessary to have an appropriate fixed asset accounting policy in accordance with PSAK No. 16. This study aims to determine how the recognition, measurement, and presentation of accounting for fixed assets based on PSAK No. 16 at the Arviel Gorontalo Hotel. This study uses qualitative approach that compares the actual situation with relevant theories related to the problem. The data obtained is the result of interviews and documentation. Analysis is done by comparing the financial statements of the Arviel Gorontalo Hotel with PSAK No. 16. The results show that the Arviel Hotel Gorontalo has not fully implemented the accounting for fixed assets in accordance with PSAK No. 16.